Near-ultraviolet circular dichroism and two-dimensional spectroscopy of polypeptides - Segatta, Francesco; Rogers, David M.; Dyer, Naomi T.; Guest, Ellen E.; Li, Zhuo; Do, Hainam; Nenov, Artur; Garavelli, Marco; Hirst, Jonathan D. (NLM (Medline), 2021)
A fully quantitative theory of the relationship between protein conformation and optical spectroscopy would facilitate deeper insights into biophysical and simulation studies of protein dynamics and folding. In contrast to intense bands in the far-ultraviolet, near-UV bands are much weaker and have been challenging to compute theoretically. We report some advances in the accuracy of calculations in the near-UV, which were realised through the consideration of the vibrational structure of the electronic transitions of aromatic side chains.